Challenges and prospects to the integration of ocean education into high school science courses in Nova Scotia. Issue 2 (2nd April 2020) - McPherson, Kerri; Wright, Tarah; Tyedmers, Peter
Abstract: Ocean education can potentially improve understanding and engage individuals to act sustainably. Within Canada, a country bordered by three oceans with vast ocean resources, there is no formal mandate to teach ocean literacy within the school system. The ocean impacts the economy, culture, and ecology of Nova Scotia. This study examines, through semi-structured interviews, the challenges experienced by high school science teachers to the integration of ocean education into science courses. Results from this study indicate that despite placing value on the ocean the main challenges teachers incurred were limited background knowledge, lack of resources, curriculum outcomes, and time constraints.